Impact and Functions of the Legend of Joko Lancur and Dewi Amirah’s Forbidden Love for the People of Ponorogo - Meliani Risdiana; Eggy Fajar Andalas; Joko Widodo (POETIKA, 2022)
The legend of the forbidden love relationship between Joko Lancur and Dewi Amirah is much more than just an oral story. This story is still believed to be true so that it affects the socio-cultural life of the Ponorogo community in Indonesia. This study aims to describe the impact and function of the legend in the life of the people of Ponorogo. This study uses a sociology of literature perspective. Data were collected through 1) observation, 2) documentation, and 3) interviews with some informants. The results showed that the legend of Joko Lancur and Dewi Amirah is still deeply rooted in the social fabric of the people of Golan Village and Mirah Hamlet in Ponorogo. This legend is believed to be true by the communities in the two regions so it has an impact on the way they view the social relations between the two regions. The people of both regions believe that members of Golan community will never be able to live together with those of Mirah community. If this taboo is violated, bad things will happen. Even so, this legend functions as a means of 1) legalizing social institutions, 2) regulating community norms, 3) supporting education, and 4) strengthening community solidarity.